2011
DOI: 10.1373/clinchem.2010.159210
|View full text |Cite
|
Sign up to set email alerts
|

Direct Saliva Transcriptome Analysis

Abstract: BACKGROUND: Current standard operating procedures for salivary transcriptomic analysis require low temperatures and lengthy mRNA isolation, which substantially hamper its use in the clinic. We developed a streamlined, ambient-temperature processing, stabilization, and storage protocol for clinical analysis of salivary RNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 23 publications
0
41
0
Order By: Relevance
“…Although the number of methods for isolating RNA from saliva has markedly increased over the years, most of the protocols remain relatively costly, owing to the predominant use of commercial kits (6 ) and, more importantly, the relatively low RNA yields. Furthermore, a large body of literature on transcriptomic studies of saliva has considered only the cell-free salivary supernatant as a biological source for isolating RNA, as opposed to the salivary cellular pellet (7)(8)(9)(10). New high-throughput RNA-isolation methods have emerged, but these methods were developed to isolate RNA from the cell-free salivary supernatant; they also require relatively large volumes of saliva.…”
mentioning
confidence: 99%
“…Although the number of methods for isolating RNA from saliva has markedly increased over the years, most of the protocols remain relatively costly, owing to the predominant use of commercial kits (6 ) and, more importantly, the relatively low RNA yields. Furthermore, a large body of literature on transcriptomic studies of saliva has considered only the cell-free salivary supernatant as a biological source for isolating RNA, as opposed to the salivary cellular pellet (7)(8)(9)(10). New high-throughput RNA-isolation methods have emerged, but these methods were developed to isolate RNA from the cell-free salivary supernatant; they also require relatively large volumes of saliva.…”
mentioning
confidence: 99%
“…Wong (2007) reported that RNALater is a poor stabilizing reagent because of its high salt content and ability to increase cellular membrane permeability, which increases the release of contaminating genomic DNA. In 2011, Lee et al (2011) described a direct saliva transcriptome analysis that successfully used an ambient-temperature processing, stabilization and storage protocol for salivary RNA. More recently, Pandit and colleagues (2013) have modified an existing Qiagen protocol (QIAzol), to provide investigators with a robust, cost-effective alternative to other commercially available RNA extraction kits.…”
Section: Salivary Collection Storage and Processingmentioning
confidence: 99%
“…The investigators performed whole transcriptomic microarray analyses on saliva samples collected from 10 subjects (six males) and identified what they coined as the Normal Core Salivary Transcriptome (NCST) (Li et al 2004a (2006) refuted the notion that salivary RNAs were detectable in human saliva, stating that signals on microarrays and RT-qPCR amplification were caused by genomic DNA contamination. However, a series of published reports have confirmed the presence of saliva mRNAs, leaving little doubt of their potential for enhancing and informing clinical care (Li et al 2004a;Hu et al 2006Hu et al , 2008Park et al 2007;Maron et al 2010;Lee et al 2011). Extracted mRNAs have been applied to multiple downstream transcriptomic platforms including microarrays (Li et al 2004a), RT-qPCR (Maron et al 2012b), and RNA sequencing (Spielmann et al 2012).…”
Section: Salivary Rna and Downstream Applicationsmentioning
confidence: 99%
“…However, this approach also involves centrifugation. An alternative method has been described [83], but it was based on the use of an expensive stabilizing agent (expensive). Thus, neither method is completely suitable for all applications.…”
Section: Clinical Application Of Salivary Diagnosis In the Era Of "Ommentioning
confidence: 99%